Analisis Dampak Covid-19 terhadap Inflasi Harga Masker - Meiriza, Mica Siar; Alvindra, Devira Chessa; Siagian, Hernita; Umamah, Nur; Situmeang, Venus; Hutagalung, Marshanda (Ikatan Da'i Indonesia, 2024)
Inflation has quite a big impact on people's purchasing power, therefore it is important for us to know what factors cause it. And there are many impacts that occur and are felt by society. Moreover, this product can be used to avoid or even prevent us from contracting the COVID-19 virus. An example is products related to health, especially masks. The aim of this research is to determine the impact of COVID-19, masks, inflation COVID-19 inflation on the price of masks. The focus of this research is to use statistical data obtained from the central statistics agency. The research method used in this research is a quantitative descriptive method. This article contains COVID-19 data on mask prices. The review concluded that the increase in mask prices had a very different impact on inflation. The price of masks which continued to soar from 2019-2023 had a big influence on mask price inflation.